Deepfake: New Era in The Age of Disinformation & End of Reliable Journalism - Erkam Temir (Selçuk İletişim, 2020)
From the very first moment of journalism, it is obvious that there are fake news and therefore reliable journalism problems. However as in many fields, rapid technological developments in the last century have had dramatic results in the field of journalism too. The perception of trust in journalism has changed and is changing. Therefore, our age is started to be mentioned as an age of disinformation. It is possible to call deepfake (video-audio manipulation technology based on artificial intelligence) as a new era in this age. As a matter of fact, with deepfake, it has become easy for even ordinary users to display it as if someone has said something they have never said or went to a place they have never been to. Although this situation has the potential to provide wide benefits in various fields, it is possible to say that it will cause big problems in many fields including journalism. Thus, in this article, using descriptive analysis method the general social problems caused by deepfakes are briefly mentioned and it is claimed that reliable journalism is at risk of disappearing if fast and effective measures are not taken.